Gen Z Job Satisfaction: Leadership, Work Communication, and Collectivism Effects - Arini Ulfa Mawaddah; Linda Linda; Dedi Muhammad Shiddiq; Tismazammi Mustofa; Tho Alang (Universitas KH. Abdul Chalim Mojokerto, 2025)
Job satisfaction plays a crucial role in professional settings, particularly as it reflects the effectiveness of individual performance and overall employee well-being. In the context of Generation Z employees working in large manufacturing industries, understanding the factors influencing job satisfaction is essential to improving productivity and retention. This study investigates the relationship between spiritual leadership style, work communication, and organizational collectivism with job satisfaction among Gen Z employees in Cirebon Regency. Specifically, it explores the moderating effect of organizational collectivism on the relationships between spiritual leadership and job satisfaction, and between work communication and job satisfaction. Data were collected through a questionnaire distributed to 200 respondents, with 181 valid responses analyzed using Moderated Regression Analysis (MRA) via SPSS. The findings reveal that both spiritual leadership and work communication significantly and positively affect job satisfaction. Furthermore, organizational collectivism strengthens these relationships, indicating its critical role in enhancing the impact of leadership and communication on job satisfaction. These insights can guide organizations in designing effective leadership and communication strategies while considering cultural dynamics to support Gen Z employee satisfaction.